UV radiation and temperature increase alter the PSII function and defense mechanisms in a bloom-forming cyanobacterium Microcystis aeruginosa - Yan, Fang; Li, Mingze; Zang, Shasha; Xu, Zhiguang; Bao, Menglin; Wu, Hongyan (Frontiers in Microbiology, 2024)
The aim was to determine the response of a bloom-forming Microcystis aeruginosa to climatic changes. Cultures of M. aeruginosa FACHB 905 were grown at two temperatures (25℃, 30℃) and exposed to high photosynthetically active radiation (PAR: 400‒700 nm) alone or combined with UVR (PAR+UVR: 295‒700 nm) for specified times. It was found that increased temperature enhanced M. aeruginosa sensitivity to both PAR and PAR+UVR as shown by reduced PSII quantum yields (Fv/Fm) in comparison with that at growth temperature (25oC), the presence of UVR significantly exacerbated the photoinhibition. M. aeruginosa cells grown at high temperature exhibited lower PSII repair rate (Krec) and sustained nonphotochemical quenching (NPQs) induction during the radiation exposure, particularly for PAR+UVR. Although high temperature alone or worked with UVR induced higher SOD and CAT activity and promoted the removal rate of PsbA, it seemed not enough to prevent the damage effect from them showing by the increased value of photoinactivation rate constant (Kpi). In addition, the energetic cost of microcystin synthesis at high temperature probably led to reduced materials and energy available for PsbA turnover, thus may partly account for the lower Krec and the declination of photosynthetic activity in cells following PAR and PAR+UVR exposure. Our findings suggest that increased temperature modulates the sensitivity of M. aeruginosa to UVR by affecting the PSII repair and defense capacity, thus influencing competitiveness and abundance in the future water environment.